Hungarian Monitoring, 30 July 1988 . [Magyar rádiófigyelő], 1988. július 30 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Iraq-Iran reconciliation Domestic Affairs: - Károly Grósz at the end of his North American tour; Reagan's message to the Hungarian people - Public Sphere club - Ministry of Social Affairs: no atomic waste burial - Saving the Jurta Theater Külpolitika: - Irak-iráni megbékélés Belpolitika - Grósz Károly befejezte észak-amerikai körútját; Reagan üzenete a magyar néphez - Nyilvánosság Klub - Szociális Minisztérium: nem lesz atomtemető - A Jurta Színház megmentésének ügye